The diaspora sonnets - De la Paz, Oliver, 1972- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
"The sonnet proves formally malleable as de la Paz breaks and rejoins its tradition throughout this collection, embarking on a broader conversation about what fits and how one adapts--from the restrained use of rhyme in "Diaspora Sonnet in the Summer with the River Water Low" and carefully metered "Diaspora Sonnet Imagining My Father's Uncertainty and Nothing Else" to the hybridized "Diaspora Sonnet at the Feeders Before the Freeze." A series of "Chain Migration" poems viscerally punctuate the sonnets, giving witness to the labor and sacrifice of the immigrant experience, as do a series of hauntingly beautiful pantoums"--